The crime of conspiracy in international criminal law - Okoth, Juliet R. Amenge, author (The Hague : T.M.C. Asser Press, 2014)
"This book looks at the relevance of conspiracy in international criminal law. It establishes that conspiracy was introduced into international criminal law for purposes of prevention and to combat the collective nature of participation in commission of international crimes. Its use as a tool of accountability has, however, been affected by conflicting conceptual perceptions of conspiracy from common law and civil law countries. This conflict is displayed in the decisions on conspiracy by the international criminal tribunals, and finally culminates into the exclusion of punishment of conspiracy in the Rome Statute. It is questionable whether this latest development on the law of conspiracy was a prudent decision. While the function of conspiracy as a mode of liability is satisfactorily covered by the modes of participation in the Rome Statute, its function as a purely inchoate crime used to punish incomplete crimes is missing. This book creates a case for inclusion in the Rome Statute, punishment of conspiracies involving international crimes that do not extend beyond the conceptual stage, to reinforce the Statute's purpose of prevention. The conspiracy concept proposed is one that reflects the characteristics acceptable under both common law and civil law systems"--Publisher's website.
Comparative analysis Conspiracy in the jurisprudence of the international criminal tribunals Customary international law Conspiracy in the statute of the International Criminal Court.
Based on author's thesis (doctoral - Humboldt University, 2012).
Keywords: International crimes; Conspiracy -- Law and legislation; Crimes, International